Learning Factories Concepts, Guidelines, Best-Practice Examples - Abele, Eberhard; Metternich, Joachim; Tisch, Michael (Springer International Publishing : Imprint: Springer, 2019)
This book presents the state of the art of learning factories. It outlines the motivations, historic background, and the didactic foundations of learning factories. Definitions of the term learning factory and a corresponding morphological model are provided as well as a detailed overview of existing learning factory approaches in industry and academia, showing the broad range of different applications and varying contents. Learning factory best-practice examples are presented in detailed and structured manner. The state of the art of learning factories curricula design and their use to enhance learning and research as well as potentials and limitations are presented. Further research priorities and innovative learning factory concepts to overcome current barriers are offered. While today numerous learning factories have been built in industry (big automotive companies, pharma companies, etc.) and academia in the last decades, a comprehensive handbook for the scientific community and practitioners alike is still missing. The book addresses therefore both researchers in production-related areas, that want to conduct industry-relevant research and education, as well as managers and engineers in industry, who are searching for an effective way to train their employees. In addition to this, the learning factory concept is also regarded as an innovative learning concept in the field of didactics.